Dactylogyrids (Platyhelminthes: Monogenea) from Sudanese Labeo spp., with a description of Dogielius sennarensis n. sp. and a redescription of Dogielius fl osculus Guégan, Lambert & Euzet, 1989 - Pravdová M.; Ondračková M.; Přikrylová I.; Blažek R.; Mahmoud Z.; Gelnar M. (Helminthologia, 2018)
Dactylogyrid monogeneans of Labeo horie Heckel, 1847 and L. niloticus (Linnaeus, 1758) (Cyprinidae) were surveyed at two sites on the River Nile in Sudan. The present study reports the presence of ten species of Dactylogyrus Diesing, 1850 and three species of Dogielius Bychowsky, 1936 based on a morphometric evaluation of the sclerotised structures. The species found include: Dactylogyrus nathaliae Guégan, Lambert & Euzet, 1988; D. rastellus Guégan, Lambert & Euzet, 1988; D. retroversus Guégan, Lambert & Euzet, 1988; D. senegalensis Paperna, 1969, D. yassensis Musilová, Řehulková & Gelnar, 2009 and five other undescribed species of Dactylogyrus. The genus Dogielius was represented by Dogielius flosculus Guégan, Lambert & Euzet, 1989; the newly identified D. sennarensis n. sp., and one undescribed Dogielius species. While D. sennarensis n. sp. resembles D. intorquens, it differs from this species and other congeners by having a longer ventral bar and anchor points and nosclerotised vagina. In addition, this study redescribes D. flosculus based on the morphology of specimens collected from L. horie. All specimens studied had a single large vagina, in contrast to the original description which reported a vagina composed of two unconnected parts. All dactylogyrid species in this study represent new host and geographical records.